Pandemic Pills: The Absence of the Body During the Pandemic and the Reconfiguration of the Body Through Art (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article aims to problematize the absence of bodies as presence during the COVID-19 pandemic, in order to demonstrate how art served as a means of resistance and erasure, allowing us to once again perceive corporeality through artistic productions. To this end, the article analyzes the Pandemic Pills project, discussing the boundaries between literature, theater, reading, performance, mise-en-scène, and perceptions of the motionless body that writes and becomes present in front of the camera through its movements. Theoretical foundations include the works of Antonin Artaud, David Le Breton, and Paul Zumthor.
Keywords: literature; performance; body; reading; COVID-19